Listening for Lucca - LaFleur, Suzanne (New York Wendy Lamb Books, 2013)
Thirteen-year-old Siena's visions of the past intensify when her family moves to the Maine coast hoping her little brother will begin speaking, and she connects with residents of the house from many years earlier who faced a similar problem
Keywords: Moving, Household -- Visions -- Maine